THE MEANINGFULNESS OF SCHIZOPHRENIC’S VERBAL LANGUAGE (MAK WAL CASE STUDY) - Sari, Reno Novita; Syafyahya, Leni; Yades, Efri (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
Generally, language disorders experienced by people with schizophrenia include speaking often interspersed with other words, creating new words, and often speaking out of context. Even so, some people with schizophrenia can still be invited to talk or communicate. This study aims to explain the characteristics and meaning of the verbal language of schizophrenics. The methods and techniques used are data provision, data analysis, and presentation data, according to Sudaryanto (2015). Tapping techniques and pancing techniques are used to obtain data. Then, the data is analyzed using the padan method and presented descriptively. The results found that there are five characteristics of the schizophrenic’s verbal language, namely incoherence, neologisms, mixed words, silences, and repetition. Then, there are three meanings of the schizophrenic’s verbal language, namely sense, tone, and intention. In this research, there is no feelings because the splitting of the soul experienced by the sufferer caused what the sufferer said was not compliant with what he felt.